The influence and impact of artificial intelligence in the consumer decision-making process: comparing Generation X with Millennials - Braga, Fábio Miguel Iglésias (2021)
Artificial Intelligence is currently considered to be one of the most emerging technologies and that will have the greatest impact on both society and companies. In addition to its use at an organizational level, in operational terms, it's also used in the way it interacts with consumers is equally important and requires attention and development. Not all people have the same adaptability for the use of new technologies and that’s why it’s important to understand the differences that different generations have on this topic. Therefore, the main objective of this dissertation is to understand the real influence and impact that the use of AI can have in the consumer decision-making process, one of the marketing components that is currently more studied by specialists in the area, comparing Generation X with Millennials. With this objective, a questionnaire was developed whose objective was to study the influence and impact that the participants would feel at each stage of the consumer purchase decision process, through the application of AI. Within the different stages of the process, fictitious scenarios were created, where the use of an AI application is implicit for a better understanding of the questions and also of the research objective. With a final sample of 211 participants, the results suggest that AI may have an influence on some phases of the process, but not on all, regardless of the generation to which the participants belong.